AI Introduction Training For Umkm In Srengseng Sawah Village To Enhance Digital Marketing - Waskita Cahya; Filda Angellia; Astrid Silvanie; Ari Kurniawan; Dwi Sidik Permana; Ghanistantiono Dwi H; B Harjo Baskoro (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
UMKM in Srengseng Sawah Village face significant challenges in digital marketing, particularly in leveraging Artificial Intelligence (AI) to optimize their strategies. Many UMKM still rely on conventional methods, lacking the knowledge and tools to harness AI for market analysis, customer engagement, and automated marketing. This community service program aims to bridge this gap by providing training and mentoring on AI applications in digital marketing. The program seeks to enhance UMKM understanding of AI in digital marketing, equip them with practical skills to use AI tools, improve their marketing effectiveness, and document the outcomes for broader dissemination. The program aims to achieve increased digital literacy among UMKM, development of a reusable training module, higher revenue through AI-driven marketing, a scientific publication, and a prototype AI-based digital platform if feasible.